2022
DOI: 10.33369/pgsd.15.1.1-12
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Pembelajaran IPS Berbasis Powtoon Terhadap Minat Belajar Siswa Kelas IV SDN Jenggot Krembung Sidoarjo

Abstract: This study aims to determine the effect of Powtoon-based social studies learning media on the learning interest of fourth-grade students at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Even other research found that educational games in general help students improve their learning outcomes, based on research results that there is an influence of the use of educational media games on the learning outcomes of class IV students of SDN Kajartenguli Prambon Sidoarjo. Educational media games can be used as a consideration for the use of alternative learning media to create an atmosphere of interesting and enjoyable learning activities (Wijayanto, E., & Istianah, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Even other research found that educational games in general help students improve their learning outcomes, based on research results that there is an influence of the use of educational media games on the learning outcomes of class IV students of SDN Kajartenguli Prambon Sidoarjo. Educational media games can be used as a consideration for the use of alternative learning media to create an atmosphere of interesting and enjoyable learning activities (Wijayanto, E., & Istianah, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mengapa tidak pergi dari tiap-tiap golongan di antara mereka beberapa orang untuk memperdalam pengetahuan mereka tentang agama dan untuk memberi peringatan kepada kaumnya apabila mereka telah kembali kepadanya, supaya mereka itu dapat menjaga dirinya". Minat adalah perasaan suka dan tertarik terhadap sesuatu atau suatu kegiatan tanpa mengatakannya (Widayanti et al, 2021) Perkembangan ilmu pengetahuan dan teknologi (IPTEK) menyebabkan semakin banyak perubahan di zaman yang bertambah canggih dan serba cepat (Prianti & Rezania, 2022). Berkembangnya ilmu pengetahuan dan teknologi khususnya teknologi informasi memberikan dampak yang besar terhadap pelaksanaan pembelajaran di sekolah.…”
Section: Pendahuluanunclassified
“…Pelaksanaan penelitian menggunakan metode show and tell sudah pernah dilsanakan sebelumnya akan tetapi sebagian besar penelitian tersebut berfokus menggunakan media berupa foto atau media lainnya, namun pada penelitian ini peneliti menggunakan bantuan media berupa video animasi. Media video animasi adalah media audio visual yang memadukan gambar animasi bergerak dan suara berdasarkan karakter animasi dengan diikuti audio sesuai dengan karakter animasi" (Rahmayanti, 2018). Manfaat dari pemanfaatn video animasi diantaranya: Proses pembelajaran lebih interaktif dan berkualitas, kualitas pengajaran dapat ditingkatkan, sikap positif siswa terhadap pembelajaran meningkat, dan memperkuat peran positif guru.…”
Section: Pendahuluanunclassified